Low temperature multi-differential operational amplifier - O. V. Dvornikov; V. A. Tchekhovski; V. L. Dziatlau; A. V. Kunts; N. N. Prokopenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A multi-differential operational amplifier, called OAmp3, designed for operation at temperatures up to minus 197 °С and developed on bipolar transistors and junction field-effect transistors of the master slice array МН2ХА030, is considered in the article. The circuitry features of the OAmp3 allow, due to the use of various negative feedback circuits, to implement a set of functions necessary for signal processing on a single amplifier: amplification (or current – voltage conversion), filtering, shift of the constant output voltage level. The performed measurements of OAmp3, connected as instrumentation amplifier circuit, showed that all manufactured products retain their performance in the temperature range from minus 150 °С to 20 °С, and individual samples – at minus 197 °С. It was found that the main reason for the loss of OAmp3 performance is an increase of the resistance of semiconductor resistors by almost 5.4 times at minus 197 °С compared to normal conditions and decrease in the junction field-effect transistor drain current. Together, these factors lead to decrease in the current consumption of the OAmp3 by almost 31 times at minus 180 °С compared to normal conditions. To reduce the temperature dependence of the current consumption and, thus, save the OAmp3 operability at low temperatures without changing the technological route of integrated circuits manufacturing, it is proposed to replace high-resistance semiconductor resistors with “pinch-resistors” formed on a small-signal p-junction field-effect transistor. The article presents the OAmp3 connection circuit in the form of an instrumental amplifier, the method and results of low-temperature measurements of experimental samples.